A meta-analysis over geometric modeling simplifications in ENVI-met urban climate simulation - Favretto, Ana Paula Oliveira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2018)
Environmental modelling requires, among other aspects, a description of the built geometry. However, the complexity of the urban tissue draws uncertainties about the building form and locations. Therefore, during the planning process generic simplified geometry models may be more appropriate than the detailed ones. This research shows a meta-analysis performed by comparing the results of detailed and simplified geometric models. The prediction deviations that may arise from using geometric simplifications on ENVI-met modelling were evaluated, considering the output data from different building typologies (one and ten-storey buildings) and urban scenarios (with and without internal squares). Three metrics were analysed: air temperature, wind speed, and sky view factor (SVF). These metrics were normalized between 0 and 1 for comparison and performance assessment. The results indicated that the most adequate simplification models are those that that have kept the building perimeter of the blocks unchanged in relation to the corresponding detailed models.